ANALISIS DAN DESAIN SISTEM PENCATATAN DATA MANIFES KAPAL PENYEBERANGAN MENGGUNAKAN METODE PIECES DAN UML - Sinaga, Tantri Hidayati (Riau Journal Of Computer Science, 2020)
Crossing shipsÂ are the main transportation in several tourism areas, including on Lake Toba and become the main choice of people around Lake Toba and Samosir Island. The Manifest Data is a very important document in the process of transportation, especially airplanes and ships, including crossing ships on Lake Toba. The manifest contains data on passengers, crew members and various items transported by the mode of transportation. Manifest documents are also useful for the process of disbursing insurance for transportation accidents. Passenger Manifest data using crossing ships on Lake Toba currently only records the number of passengers and the number of vehicles boarding the ship, but does not record details of the identity of the passenger and vehicle. The application of recording passenger manifest data is needed to manage the manifest data of crossing ship passengers on Lake Toba, with the aim of facilitating monitoring of crossing activities and the process of identifying passenger crossing ships. This research will conduct an analysis and design of the crossing vessel Manifest Passenger Manifest recording system in Lake Toba. The system is made web-based, so it will be easily accessed anywhere, and can only be accessed by the North Sumatra Transportation Office. This application can be used to make it easier for the parties involved in supervising and controlling the list of boat passengers who travel on Lake Toba, so that it can reduce the risk of accidents and misuse of the number of boat loads from the permit